Confinement of Suspension-Cultured Cells in Polyethylene Glycol/Polyethylene Oxide-Albumin Aqueous Two-Phase Systems - Teixeira, Alyne G.; Kleinman, Alex; Agarwal, Rishima; Tam, Nicky W.; Wang, Jun; Frampton, John P. (Frontiers in Chemistry, 2019)
Aqueous two-phase systems (ATPSs) have numerous applications in separation science, and more recently, in bioassays enabled by the solution micropatterning of cells. The most frequently used ATPS in these applications is the polyethylene glycol (PEG)-dextran (Dex) system, as the polymers that form this ATPS have been extensively characterized in terms of their physicochemical properties. However, in addition to this well-known system, there exist many other ATPSs with properties that may be exploited to improve upon the PEG-dextran system for specific applications. One of these underexplored systems is the ATPS formed from PEG/polyethylene oxide (PEO) and albumin. In this article, we characterize the phase separation of PEG (35 kDa) and polyethylene oxide (PEO) (200 kDa, 900 kDa and 4,000 kDa) with bovine serum albumin (BSA). We describe the microscopic emulsion behavior of these systems in the presence of NaCl and compounds (NaHCO3, NaH2PO4 and HEPES) commonly used in buffer solutions and cell culture media. We further demonstrate that PEG- and PEO-albumin systems can be used in place of the PEG-dextran system for confinement of suspension-cultured cells (Jurkat T cells). Cell viability and morphology are examined for various polymer formulations relative to the commonly used PEG 35 kDa-Dex 500 kDa system and polymer-free cell culture medium. In addition, we examine cell activation for various phase-separating medium components by measuring IL-2 secretion. We demonstrate that the PEG- and PEO-albumin systems represent promising ATPS formulations for applications where low levels of baseline cell activation are required.